Bonding Trends in Tetravalent Th–Pu Monosalen Complexes. Issue 70 (9th November 2020) - Radoske, Thomas; März, Juliane; Patzschke, Michael; Kaden, Peter; Walter, Olaf; Schmidt, Moritz; Stumpf, Thorsten
Abstract: The synthesis of three complex series of the form [AnCl2 (salen)(Pyx)2 ] (H2 salen= N, N′ ‐bis(salicylidene)ethylenediamine; Pyx=pyridine, 4‐methylpyridine, 3, 5‐dimethylpyridine) with tetravalent early actinides (An=Th, U, Np, Pu) is reported with the goal to elucidate the affinity of these heavy elements for small neutral N‐donor molecules. Structure determination by single‐crystal XRD and characterization of bulk powders with infrared spectroscopy reveals isostructurality within each respective series and the same complex conformation in all reported structures. Although the trend of interatomic distances for An−Cl and An−N (imine nitrogen of salen or pyridyl nitrogen of Pyx) was found to reflect an ionic behavior, the trend of the An−O distances can only be described with additional covalent interactions for all elements heavier than thorium. All experimental results are supported by quantum chemical calculations, which confirm the mostly ionic character in the An−N and An−Cl bonds, as well as the highest degree of covalency of the An−O bonds. Structurally, the calculations indicate just minor electronic or steric effects of the additional Pyx substituents on the complex properties. Abstract : Th–Pu IV salen complexes : A series of monosalen complex with Th–Pu IV has been synthesized and characterized in the solid state and with quantum chemical (QC) calculations. They reveal the salen's potential to provide a fixed binding pocket to An IV, allowing a facile exchange of pyridine‐based solvents in the labile positions. Differences in binding strength explain the findings: all An IV −N are of mostly ionic nature but An IV −O have a significant covalent contribution.